Haplotype distribution among endangered asian elephants (Elephas maximus) in Peninsular Malaysia - Elliza, M.N.; Shukor, M.N.; Othman, N.; Md-Zain, B.M. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Asian elephants are classified as an endangered species on the IUCN red list, warranting more research and conservation efforts to protect them. A study of the distribution of haplotypes among Asian elephants in Peninsular Malaysia was performed using a partial DNA sequencing of a D-loop region. In this study, 10 haplotypes (Hap01–Hap10) were detected in Peninsular Malaysian populations with a high haplotype diversity (Hˆ ) of 83%. Hap01 was shared by Kelantan (n = 1), Johor (n = 2), Pahang (n = 2), and Perak (n = 2). The other shared haplotype was Hap06, which was evident in the Pahang (n = 1) and Johor (n = 1) samples. DnaSP analysis demonstrated that low genetic diversity (π) was observed in Peninsular Malaysian elephants (0.55%). Conversely, the gene flow was high (Nm = 9.65 migrants per generation). In a test of population subdivision, all pairwise comparisons for Peninsular Malaysia were low (0.00 to 0.13) except for Kelantan–Pahang (0.57). Our results demonstrated that the genetic diversity was low within the different populations of Peninsular Malaysia. The level of genetic differentiation was also low, but the gene flow was high regardless of the geographic distance of the Asian elephant populations in Peninsular Malaysia.